The Role of TCA Cycle Anaplerosis in Ketosis and Fatty Liver in Periparturient Dairy Cows - White, Heather M. (Animals (Basel), 2015)
The transition to lactation period in dairy cattle is characterized by metabolic challenges, negative energy balance, and adipose tissue mobilization. Metabolism of mobilized adipose tissue is part of the adaptive response to negative energy balance in dairy cattle; however, the capacity of the liver to completely oxidize nonesterified fatty acids may be limited and is reflective of oxaloacetate pool, the carbon carrier of the tricarboxylic acid cycle. Alternative metabolic fates of acetyl-CoA from nonesterified fatty acids include esterification to triacylglycerides and ketogenesis, and when excessive, these pathways lead to fatty liver and ketosis. Examination of the anaplerotic and cataplerotic pull of oxaloacetate by the tricarboxylic acid cycle and gluconeogenesis may provide insight into the balance of oxidation and esterification of acetyl-CoA within the liver of periparturient dairy cows.